Enhancing User Satisfaction and Loyalty in MSMEs: The Role of Accounting Information Systems - Imtihan, Khairul; Mardi, Mardi; Tantoni, Ahmad; Bagye, Wire; Zulkarnaen, Muhammad Fauzi (Universitas Bina Darma, 2025)
This study examines the impact of Accounting Information System (AIS) attributes on User Satisfaction, Decision-Making, and Loyalty among Micro, Small, and Medium Enterprises (MSMEs). The research evaluates how Content, System Quality, Information Quality, and User Characteristics influence satisfaction and decision-making, ultimately shaping user loyalty. A quantitative approach utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze responses from 62 MSME operators in East Lombok, Indonesia. The findings indicate that Content and System Quality significantly enhance User Satisfaction and Decision-Making, which in turn mediate their effects on User Loyalty. Contrary to conventional expectations, Information Quality has a minimal impact, suggesting that MSMEs prioritize system usability and functionality over informational attributes. The study reinforces the critical mediating roles of satisfaction and decision-making, highlighting how system attributes influence behavioral outcomes. In practical terms, AIS should be designed with simplicity, reliability, and relevance to MSME needs, ensuring ease of adoption and operational efficiency. Policymakers are encouraged to promote digital literacy and provide affordable AIS solutions to accelerate adoption among MSMEs. Additionally, the study suggests that future research explore broader cultural and organizational dynamics affecting AIS adoption and employ mixed-method approaches for deeper insights into user behavior.